Dalits Cultural Spaces and Contested Culture in Punjab: Relocating the Ravidass Deras and Ad Dharmi Jatheras. (December 2019) - Singh, Surinder
The article argues that that often the marginalised sections per se and dalits, in particular, configure and shape a web of new socio-cultural traits, artefacts and monuments which provide them distinct social and physical spaces to contest the suppression of mainstream culture which historically placed them at the periphery. New dalit cultural spaces are politically constructed which have become the venues of their identity formation, construction of contested culture and cultural assertion. Their incessant segregation from mainstream cultural spaces has become a vehicle to seek new socio-cultural spaces either within or outside the mainstream social structure of the society. This process of new socio-cultural spaces formation is ultimately harnessed with the construction of contested cultural spaces. In Punjab, since the 20th century, the construction of new socio-religious spaces and identities has become the modus among the dalits to disassociate from disparaging spaces and identities.